Manejo de problemas de comportamento de crianças com transtorno do espectro autista: estudo piloto baseado em um programa de psicoeducação comportamental - Silva, Naiara Adorna da (2016)
Autism Spectrum Disorder (ASD) is one of the conditions that causes most damage to a child’s neurodevelopment. When caregivers are not provided with strategies of intervention/amelioration/prevention of behavior problems, the task of taking care becomes an overload. The general objective of this study was to verify empirical evidences of the efficiency of a psychoeducational program for parents to manage behavioral difficulties of children with ASD. The sample was composed of 8 boys with ASD, aged from 5 to 11 years (mean 8 years; standard deviation 1,93), and their respective caretakers, aged from 22 to 63 years old (mean 38,4; standard deviation 15, 95). The parents data collection instruments were: a) Form to assess demographic and socioeconomic data; b) Adult Self-Report for Ages 18-59 and Older Adult Self-Report for Ages 60 and Above (ASR/18-59 and OASR/60-90+); c) Parental Style Inventory (PSI); d) World Health Organization Quality of Life WHOQOL-bref; e) Questionnaire on the main difficulties parents/caretakers have; f) Checklist for control of program orientations; g) Questionnaire on caretakers satisfaction with the program; h) Diary record monitoring; i) Psychoeducational program for parents, which had the objective of orienting parents on the characteristics of the disorder, educating them on the use of strategies to manage behavior problems and informing on empirically tested behavior intervention strategies. Data collection instruments of children behavior were a) Child Behavior Checklist for Ages 1½-5 and for Ages 6-18 (CBCL/1½5 and CBCL/6-18); b) Behavior Problems Inventory (BPI-01); c) Aberrant Behavior Checklist (ABC); d) Questionnaire on use of mental health services. The program consisted of eight meetings, held once a week, with duration of 3 hours each (total 24 hours). Participants were assessed before, during and after the intervention. The main results indicate high adherence and satisfaction with the program, as well as a positive assessment of the possibility of employing in their routine the orientations received in the program. Positive empiric evidences were found in the behavioral and mental health patterns of the children and caregivers, as well as in their quality of life.